Proventricular morphopathology in wild ducks (Anas discors) infested with Tetrameres americana - Colas C., Manuel (2016)
The aim of this study was to describe the morphopathological changes in proventriculus of wild ducks (Anas discors) infested with Tetrameres americana. Necropsy to 89 cadavers of adult ducks from Pinar del Río, Cuba, was performed. Samples of 1 cm2 from 22 proventriculi diagnosed with parasitic proventriculitis were taken for the histopathological study. All proventriculi ducts were collected for parasitological analysis and the lesions were classified as mild and severe according to the amount of glands affected with the nematode and the magnitude of catarrhal exudate. The results showed that 25% (22/89) of the ducks had proventriculitis caused by T. americana where 73% of the cases was considered as mild. Mucosal erosion, degeneration with necrosis and formation of nodules of 1 cm of diameter in the glandular yolk were observed. It is concluded that infestation with T. americana causes morphopathological lesions in proventriculus of A. discors.